A Web-Based XR Platform for Offshore Safety Training: Design and Evaluation - Porcino, Thiago; Cherullo, Renato; Azevedo, Thiago; Goncalves, Flávia; Seixas, Luiza; Kronemberger, Victhor; Carvalho, Felipe; Raposo, Alberto (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This paper introduces a collaborative immersive training platform designed to enhance offshore safety training by integrating 360-degree panoramic imagery and Extended Reality (XR) technologies. The platform offers a web-based environment that is accessible in both immersive (virtual reality) and non-immersive (desktop) modes, allowing users to experience and respond to realistic hazardous offshore scenarios. The development process followed a user-centered design methodology, incorporating feedback from 159 health, safety, and environment (HSE) professionals and offshore workers to address everyday stressors and training limitations. To evaluate cognitive workload, a study was conducted with 156 participants using the NASA-TLX questionnaire. Findings indicate a moderate overall workload, with elevated scores for mental demand and effort, and lower scores for physical demand and frustration. Participants reported high satisfaction with the platform’s clarity and engagement, as well as positive performance outcomes. Furthermore, a qualitative analysis of emotional responses highlighted the importance of confidence, social support, and realistic challenges in creating compelling and engaging training experiences.